School Leaders' Crisis Leadership Competencies and their Pandemic Response Strategies: The Case of DEPED Division of Northern Sumar - Vicky R. Catubig (Universidade Estadual de Alagoas, 2023)
Based on the Meta-Leadership Model of Marcus et al. (2007), as cited by Saltz (2017), this research documented and assessed the crisis leadership competencies and pandemic response strategies of school leaders in the DepEd Division of Northern Samar. Utilizing a sequential exploratory approach, qualitative and quantitative designs were adopted. Thus, in the qualitative component, eight (8) school leaders participated in face-to-face interview sessions, wherein the emerging themes from their responses highlighted the concept that meta-leaders have a higher effect than their real authority because they exert a strong influence on their followers, aiding them in overcoming obstacles and seizing opportunities. They understood the nature and significance of the situation, and in order to keep a diverse group of people on track, they weaved together key themes that highlighted the organization's core purpose and ambitions. In the qualitative aspect, the broader population of 130 respondents answered a questionnaire about school leaders' crisis leadership competencies, which revealed the following results: "Very High" on Team Leadership (AWM =3.25); "High" on Situational Awareness and Integrative Thinking (AWM =3.18); and "High" on Decisiveness and Emotional Effectiveness (AWM =3.24). In addition, respondents completed a questionnaire regarding the extent of the school leader's pandemic response strategies, which revealed the following findings: Promoting Organizational Resilience, "Large Extent" (AWM =3.24); Acting with Integrity, "Very Large Extent" (AWM =3.29); and Exhibiting Learning Orientation, "Large Extent" (AWM =2.96). based on the results, the researcher contends that when establishing a crisis management plan for a successful pandemic response strategy, school leaders must prioritize the following elements: communication, high productivity, technology use, and accessibility. On the basis of these factors, the current researcher proposes the following three focus areas for the crisis management plan: (1) establishing guidelines or policies for remote work for faculty and staff; (2) embracing remote work for department heads, master teachers, and focal persons; and (3) developing inclusive and collaborative virtual meetings. The researcher also suggests that school administrators think about adopting the recommended crisis management plan to make sure that all important aspects of the school system are taken care of.